Desa Adat and Policy: Local Values, Environmental Balance, and Transactional Politics - Kusnadi, Iwan Henri; Wawan, Wawan (Journal of Governance, 2025)
The rights of origin and traditional rights of Indigenous Peoples are aspects mandated by law to be recognized and protected as the basis of recognition. However, these rights are often misunderstood by the state in the formation of customary villages or the management of indigenous communities, resulting in many traditional communities (Indigenous Society) not receiving full recognition. The state often views the issues of indigenous communities administratively, without touching on abstract aspects such as local values, which results in misguided policies. This phenomenon occurs among Indigenous communities in Lebak Regency, where the establishment of customary villages, instead of strengthening customary rights, is caught in the tug-of-war of elite political interests. This discourse shows that asymmetric democracy, which should be an inclusive mechanism, instead creates negative implications such as the politicization of customs, the erosion of local values, the disruption of ecological balance, and the introduction of transactional politics. This article dissects the dynamics of the formation of customary villages through the perspective of asymmetric democracy, highlighting its implications for local values, ecosystem balance, and political practices. Using qualitative methods with a phenomenological approach, this article seeks to explore the meaning of the experiences of Indigenous Communities in Lebak Regency in facing the challenges of democracy and the recognition of customary rights. This study found that the establishment of customary villages in Lebak Regency, which was expected to strengthen the recognition of customary rights, is instead influenced by the tug-of-war of political interests, thereby threatening local values and environmental balance and encouraging the politicization of customary practices within the framework of asymmetric democracy.